Method development for Quantification of (S) - Isomer in Tenofovir Disoproxil Fumarate Bulk Drug and Formulations using Meta Substituted Phenyl Carbamate of Amylose as Chiral Selector (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The present paper involves developing a novel Chiral ultra-high performance liquid chromatographic (UPLC) technique for estimating Tenofovir Disoproxilfumarate (TDF) enantiomeric purity in both bulk and bulk dosage forms. The TDF is a pro drug employed in treating HIV in which the (R) isomer is active, while (S) isomer remains impurity and pharmacologically inactive. The UPLC method is categorized as a green chromatographic technique in which the chiral separation was achieved on ChiralpakIG-3(2.1x100mm) 3.0μm immobilized amylose column with meta substituted 3 chloro, 5 dimethyl phenyl carbamate as chiral selector, at a flow rate of 0.5ml/min using 0.5% diethylamine as an additive in hexane and ethanol. The influence of chiral additives and organic modifiers on enantio separation was investigated. The separation was analyzed on different columns for maximum resolution>10.0. The method was linear between within 0.25 to 7.5 μg.mL−1. The detection and quantification limits of (S) isomer were 0.08 μg.mL−1 and 0.25 μg.mL−1, respectively. Forced degradation studies were conducted and all the degradants were separated from drug peak. ICH guidelines validated the method.